ANALISIS STRATEGI BISNIS PERUSAHAAN JASA TELEKOMUNIKASI PT XL AXIATA TBK - , Suhartanto Raharjo ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Currently, trends in telecommunications industry are experiencing a very significant development in terms of increasing both players and users. Total companies that compete in the business of mobile operators in Indonesia amounted to 10 operators with users that already touched 190 million people or more than 80% of the population of Indonesia. This figure shows that currently the telecommunications business is approaching saturation, but on the other hand, technologies in telecommunications still in development stage so there will new technologies or new features in future. Therefore, there should be analysis of business strategy for mobile operators to compete in the telecommunications industry. In this study will be conducted business strategy analysis at operator telecommunication PT XL Axiata which is the three major cellular players of Indonesia. External and internal analysis done to be able to formulate a business strategy that best suits at PT XL Axiata. External analysis was done by analyzing the general environmental conditions and industrial environment using the five forces and competitor analysis to identify key success factors in the telecommunications industry in Indonesia. Internal analysis carried out by analyzing the internal condition of PT XL Axiata using value chain analysis of the resources and capabilities as well as using VRIO analysis to identify the sustainable competitive advantage which is owned by PT XL Axiata. By applying an external and internal analysis to formulate business strategies PT XL Axiata in competing in the telecommunications industry in Indonesia is obtained the result that the business strategy that best suits the conditions of PT XL Axiata is Best Cost Provider Strategy. Best Cost Provider Strategy focuses on differentiation and cost leadership which is the company's sustainable competitive advantage and adapt to the key success factors in the Telecommunications Industry.